2018
DOI: 10.5455/jjcit.71-1512555333
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery EEG Signal Processing and Classification using Machine Learning Approach

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The method was based on the estimation of true covariance matrices of each motor imagery task. In another study, Sreeja et al [50] revealed that selection of 30 electrodes placed on premotor cortex, supplementary motor cortex, and primary motor cortex in combination with Despite the demonstrated possibility of optimization techniques to significantly increase classification accuracy, they strongly depend on initial data features, which along with motor-related features include other patterns related to individual subject characteristics that require preliminary calibration of the classifier for each subject. According to this fact, in our study, we propose the optimization method based on the motor-related EEG features based on the spatiotemporal and time-frequency EEG analysis in the group of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The method was based on the estimation of true covariance matrices of each motor imagery task. In another study, Sreeja et al [50] revealed that selection of 30 electrodes placed on premotor cortex, supplementary motor cortex, and primary motor cortex in combination with Despite the demonstrated possibility of optimization techniques to significantly increase classification accuracy, they strongly depend on initial data features, which along with motor-related features include other patterns related to individual subject characteristics that require preliminary calibration of the classifier for each subject. According to this fact, in our study, we propose the optimization method based on the motor-related EEG features based on the spatiotemporal and time-frequency EEG analysis in the group of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, when assessing each applicant feature subset, the wrapper method must train and test the classifier, and that is prone to overfitting and computationally costly. The embedded technique incorporates feature selection into the classifier's training phase, performing both tasks concurrently [36,37]. Although proven to be efficient in most studies, the embedded technique has the highest computational cost in all three feature selection methods.…”
Section: Introductionmentioning
confidence: 99%